2009
DOI: 10.1088/0957-4484/20/8/085202
|View full text |Cite
|
Sign up to set email alerts
|

Carrier transport mechanisms of bistable memory devices fabricated utilizing core–shell CdSe/ZnSe quantum-dot/multi-walled carbon nanotube hybrid nanocomposites

Abstract: Transmission electron microscopy images showed that conjugation between single core-shell CdSe/ZnSe quantum dots (QDs) and oxidized multi-walled carbon nanotubes (MWCNTs) was achieved through the complexation reaction. Current-voltage (I-V) measurements on Al/CdSe:MWCNT conjugated nanocomposite/indium-tin-oxide devices at 300 K showed that the on/off ratio of the current bistability was as large as about 10(4), which was significantly increased due to an enhancement of the carrier transfer efficiency between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 20 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…Oh et al reported that InAs/GaAs quantum dot layers decrease the THz power absorption and conductivity, suggesting that the quantum dots act as carrier traps and capture the mobile carriers . Recently, the electrical conductivity of CdSe/ZnSe quantum dot−MWNT hybrid nanostructures was measured to show that the quantum dots act as carrier traps . Therefore, all three types of NC would consistently serve as carrier (electron) traps on the CNT and GO.…”
Section: Resultsmentioning
confidence: 99%
“…Oh et al reported that InAs/GaAs quantum dot layers decrease the THz power absorption and conductivity, suggesting that the quantum dots act as carrier traps and capture the mobile carriers . Recently, the electrical conductivity of CdSe/ZnSe quantum dot−MWNT hybrid nanostructures was measured to show that the quantum dots act as carrier traps . Therefore, all three types of NC would consistently serve as carrier (electron) traps on the CNT and GO.…”
Section: Resultsmentioning
confidence: 99%
“…The devices based on the CdSe nanoparticles exhibit a high on/off ratio and demonstrate read‐only and random‐access memory applications. The memory phenomenon has also been found in CdSe/ZnS nanoparticles sandwiched between C‐60 layers,94 CdSe/ZnS nanocrystals in TiO 2 thin films,95 core/shell CdSe/ZnSe quantum dot/multiwalled carbon nanotube hybrid nanocomposites,96 CdTe/CdSe core/shell nanoparticles/poly(methylmethacrylate) nanocomposites,97 and CdSe nanoparticles/poly(methyl methacrylate) (PMMA) blend 98…”
Section: Novel Properties and Applications Of Cdsementioning
confidence: 92%
“…Kim et al reported a bistable memory device utilizing the self-assembled conjugations of CdSe/ZnSe core–shell QDs onto the multiwall carbon nanotubes by the complex reaction . With the CdSe/ZnSe QDs, the resistive switching voltage was significantly reduced from 1.6 to 1.1 V. Electrons injected from the electrodes transported along the carbon nanotubes.…”
Section: Building Memristor Devices With Qdsmentioning
confidence: 99%